Droplet interface in additive manufacturing: From process to application. Issue 2 (10th April 2023) - Sun, Zhengnan; Zeng, Xu; Deng, Xu; Zhang, Xiaosheng; Zhang, Yi
Abstract: Additive manufacturing (AM), which is often referred to as three‐dimensional printing, revolutionizes manufacturing by providing a high degree of design freedom and customization. Several AM methods entail precise control of droplet interfacial properties to ensure the high quality of the printed products. At the same time, the rapid growth of AM technology has made it possible to prepare novel surfaces with complex structures, further expanding the range of potential applications of droplet interface. To provide a unified framework to guide the continuous development of AM that involves droplet interface, this manuscript reviews related work in this field from two aspects—the droplet interface phenomenon in AM processes and the applications of droplet interface prepared by AM. Limitations of existing works are discussed, and potential future directions are suggested. Abstract : Droplet interface in additive manufacturing (AM): Droplet interfacial phenomena during AM and application of the droplet interface prepared by AM.